Pengaruh keberadaan logo halal dan kualitas keripik tempe terhadap keputusan pembelian konsumen [Influence of halal logo existence and quality of tempe chips on consumer purchasing decisions] - Sucipto, Sucipto; Kusumastuti, Nastiti Putri Ayu; Islami, Fenti Nur Addina; Septifani, Riska (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
Halal food demand rises in line with the increasing Muslim population. Sanan Industrial Center in Malang City produces tempe chips, both halal- certified and not halal-certified. Generally, the purchase of a product is influenced by the halal logo and its quality. The research objective was to determine halal logo existence and tempe chips' quality on purchasing decisions and provide alternative improvements. The research used the Partial Least Square (PLS) method. The results showed that the existence of the halal logo and product quality affected the purchase decision of both halal-certified and not halal-certified tempe chips. The most influencing variables on halal-certified tempe chips' purchase decision were conformance, aesthetics, halal logo, and performance. The order of the most influencing variables on purchasing decisions for tempe chips products that were not certified halal was conformance, performance, and the existence of a halal logo. Tempe chips business needed to carry out halal certification or halal recertification to include the halal logo on the packaging. Product performance could be improved by innovation and packaging design to make it more attractive.